2015
DOI: 10.1021/acssuschemeng.5b00939
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Improvement in the Stability of Hemoglobin in the Presence of Promising Green Solvent 1-Allyl-3-methylimidazolium Chloride

Abstract: In this article, we have explored the influence of peculiar member of imidazolium-based ionic liquid (IL) 1-allyl-3-methylimidazolium chloride ([Amim][Cl]) on the stability of haemoglobin (Hb) by using fluorescence, thermal fluorescence, ANS fluorescence, circular dichroism (CD) spectroscopy and dynamic light scattering (DLS) measurements. In the attempt of searching of IL which can provide stability to Hb, for the first time, we have successfully shown the stability of Hb in [Amim][Cl]. Our results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…The addition of ionic liquids (ILs), which have emerged as a promising solvent, strengthen the stability of biomolecules like proteins, enzymes and DNA . Recent studies have shown that ILs can influence the protein activity and stability, improve refolding, and inhibit the aggregation …”
Section: Introductionmentioning
confidence: 99%
“…The addition of ionic liquids (ILs), which have emerged as a promising solvent, strengthen the stability of biomolecules like proteins, enzymes and DNA . Recent studies have shown that ILs can influence the protein activity and stability, improve refolding, and inhibit the aggregation …”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, it has been observed that selected ILs are able: (1) to kill bacteria and cancer cells while leaving eukaryotic healthy cells almost unaffected; (2) to extract, purify and even preserve DNA at ambient temperature; (3) to stabilize proteins and enzymes; (4) to either favour or prevent protein amyloidogenesis; (5) to penetrate and eventually disrupt biomembranes via extended poration; and (6) to dissolve polysaccharides and cellulose. A recent overview of the subject is reported in two reviews authored by Benedetto and Ballone (2016a, b).The aim of the BIonic Liquid meet Biomolecules^session of the IUPAB-EBSA congress was to present an up-to-date overview of this new and intriguing subject of research which has potential applications in several fields, ranging from biomedicine, pharmacology, and material science to bionanotechnologies.Pannuru Venkatesu (University of Delhi, India) focuses on the interaction between ionic liquids and proteins (Meena et al 2016;Jha and Venkatesu 2016), arguing that studies of interaction between proteins and different ILs in aqueous solution are comparatively more important than those in pure ILs. The results of these investigations suggest that the ILwater-protein interaction is a complex balance of different contributions by the different components, which is not possible to predict a priori.…”
mentioning
confidence: 99%
“…Pannuru Venkatesu (University of Delhi, India) focuses on the interaction between ionic liquids and proteins (Meena et al 2016;Jha and Venkatesu 2016), arguing that studies of interaction between proteins and different ILs in aqueous solution are comparatively more important than those in pure ILs. The results of these investigations suggest that the ILwater-protein interaction is a complex balance of different contributions by the different components, which is not possible to predict a priori.…”
mentioning
confidence: 99%
“…This will not only increase the shelf life of insulin, whereas suitable formulations of insulin in biocompatible ILs can lead to safe and durable insulin formulations in pharmaceutical products. The ammonium-based ILs such as ethylammonium mesylate (EaM), diethylammonium mesylate (DeaM)-stabilized tobacco mosaic virus, whereas triethylammonium mesylate (TeaM) caused a change in the secondary structure of the virus[149].From the literature and from our own experience, it can be suggested that ammonium-based ILs are more biocompatible as compared to the imidazolium-based ILs[44,[140][141][142][143][144][145][146][147][148][149][150][151][152][153][154][155]. Yu et al [150] explored the stability of laccase in the presence of both ammonium-and imidazolium-based ILs such as [TMA][TfO], [Bmim][TfO] and [Bmpyr][TfO].…”
mentioning
confidence: 99%
“…The contrasting nature of ammonium family ILs is also consistent with Rodrigues et al[151], where among different families of ILs only ammonium-containing IL shows higher activity as compared to imidazolium-based ILs for Thermomyces lanuginosus lipase (TlL). Scheme 2 shows the difference between the biocompability behaviors of ammonium-and imidazolium-based ILs.On the other hand, Jha et al[152] have explored the influence of a of imidazolium-based IL, 1-allyl-3-methylimidazolium chloride ([Amim][Cl]), on the stability of Hb. Unprecedented improvement in the stability of Hb in the presence of [Amim][Cl] at the lower concentration of [Amim][Cl] was…”
mentioning
confidence: 99%